The GSCPI: A new barometer of global supply chain pressures - Gianluca Benigno; Julian Di Giovanni; Jan J. J. Groen; Adam I. Noble (Federal Reserve Bank of New York, 2022)
We propose a novel indicator to capture pressures that arise at the global supply chain level, the Global Supply Chain Pressure Index (GSCPI). The GSCPI provides a new monitoring tool to gauge global supply chain conditions. We assess the index's capacity to explain inflation outcomes, using the local projection method. Our analysis shows that recent inflationary pressures are closely related to the behavior of the GSCPI, especially at the level of producer price inflation in the United States and the euro area.
Keywords: F40; F10; F20; 330; global supply chain; inflation; transportation costs